Reproductive Health of Women Workers in Villages, Cities in Islamic Perspective - Tri Niswati Utami; Nurhayati Nurhayati; Reni Agustina Harahap; Zuhrina Aidha (Humanistic Network for Science and Technology (HNST), 2020)
The trend of working women in Indonesia has increased. In 2017 the participation rate of women workers increased by 39.3%. This study aims to analyze the tendency of women to work in villages and cities, analyze the relationship of women who work with reproductive health, the relationship between marital status and reproductive health and Islamic perspectives on working women. The method used was quantitative, sourced from secondary data on Indonesia's Demographic and Health Data Survey 2017 Data were analyzed using the chi-square test. It was found that the tendency of women to work in villages was higher by 65.5%. The analysis found that the significant correlation between job status and marital status with reproductive health, with p-value of 0.0001 and 0.0001. It is not forbidden in Islam that women work outside the home, but must uphold a woman’s character, her role in her family and dignity. Considering women have a dual role, in the household and as workers, the company should give the right to maintain reproductive health such as menstruation leave, pregnancy, childbirth, and breastfeeding. Keywords: female workers; types of work; reproductive health; marital status; village